Brexit and Change Management: A Case Study of the Royal Bank of Scotland - Saddam Rassanjani (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Change is a sure thing to happen in company management, both because of internal factors and external factors. The Brexit decision taken by the UK certainly has an impact on the economic sector, including the banking sector which has long been the mainstay of this commonwealth country. In analyzing strategic change management, the author takes the Royal Bank of Scotland (RBS) as the object of study, where this case study is analyzed through the change model from John Kotter. The change management adopted by RBS in the face of Brexit is illustrated through eight stages of change according to what John Kotter described.